Thermodynamic Study of Metal Complexes of Mixed Morpholine-thiocyanate and Isothiocyanate - M. Alam, MD.; Kazmi, A.H.; Sinha, H.K.; Singh, V.P. (Asian Journal of Chemistry, 2010)
Thermodynamic study has been made to know the stability of mixed morpholine-thiocyanate and isothiocyanate complexes of Zn2+, Cd2+ and Hg2+ ions. In this connection, the study based on thermodynamic parameter indicates that (—SCN) complexes of these metals are more stable than (—NCS) complexes.